Modes of iron-manganese mineralization on the bottom of lake Baikal. - Baturin, Gleb N; Peresypkin, Valery I; Zhegallo, E A (PANGAEA, 2011)
The investigation of the Baikal Lake bottom carried out during summer 2008 by means of the Mir deep-sea manned submersibles resulted in sampling of a series of sediments, ferruginous crusts, and peculiar mineralized tubes several centimeters high and up to 2-6 cm in diameter. According to scanning electron investigation they consist mainly of enclosing sediment particles and biogenic silica cemented by iron and minor manganese hydroxides. Chemical composition of the tubes is similar to ones of both host sediments and slightly ferruginous crusts and nodules, but the tubes and crusts are somewhat richer relative to sediments in some microelements, namely, arsenic, cadmium, and uranium. In general, structure and composition of these tubes remind one of worm tubes common in sediments of some seas. Investigation rare earth elements in some samples or ferruginous manifestations and bottom sediments revealed a positive europium anomaly, which might be related to either composition of surrounding continental magmatic rocks or to influence of hypothetical hydrothermal solutions.
Composition of bottom sediments and ferruginous bottom manifestations from the Baikal Lake
Keywords: Archive of Ocean Data; ARCOD; Baikal Lake; BPZ-B-40; BPZ-B-41; BPZ-B-44; BPZ-B-59; BPZ-B-67/4; BPZ-B-68/5; MIR; MIR deep-sea manned submersible